Exploring the Challenges and Opportunities of AI in Decision-Making in Construction Project Management - Bikwa, G.; Bond-Barnard, T.J. (The South African Journal of Industrial Engineering, 2025)
This research explores the integration of artificial intelligence (AI) in construction project management, emphasising its effect on decision-making. While AI offers substantial potential to improve efficiency and optimise resources, its adoption in the construction industry faces notable challenges. This study bridges the gap between AI’s theoretical potential and its practical application by exploring how it could transform decision-making in resource management, risk assessment, and project scheduling. Using qualitative methods and thematic analysis, the research evaluates current AI usage, identifies key roles, and analyses both difficulties and opportunities. The findings contribute to AI ethics and project management by providing practical guidelines for AI adoption in construction. The study concludes that AI could significantly improve decision-making accuracy, speed, and efficiency, but acknowledges barriers such as high implementation costs, skill shortages, and data quality issues. This comprehensive analysis offers valuable insights into and recommendations for the integration of AI into construction project management.